The othering of the colonial subject in Danticat and Kincaid: comparative analysis - Targino de Castro Nunes, Anna Júlia; Sá, Nicole Anizio Mariano de; Mendes, Maria Elizabeth Peregrino Souto Maior (The ESPecialist, 2024)
The objective of the present article is to investigate the diasporic experience of the female subjects represented in the novella Lucy, by Jamaica Kincaid, and in the short story “Children of the Sea”, by Edwidge Danticat. Sharing Afro-Caribbean origins, Kincaid from Antigua and Barbuda, and Danticat from Haiti, the writers problematize, in their ouvre, the diasporic processes of the colonized subjects, their experiences as human beings marked by ethnic features, specific social roles and determined cultural expectations. Kincaid’s novella Lucy and Danticat’s short story “Children of the Sea”, make explicit the political motivations of the migrant subjects in a journey to freedom and debate the difficulties of the bodies marked by the colonial heritage of having their human rights assured in a country which sees them only as second-class citizens. Therefore, we intend to analyze the ways in which the experiences of the characters Lucy and Célianne are affected by their identity as black colonized women. Both narratives expose not only the deleterious effects of colonialism, but also the othering and subordination of the black body, and mainly how it reacts to the processes of marginalization and dehumanization they are subjected to. As theoretical framework, the proposed analysis is grounded on the studies of Davis (1981), Lorde (1984), Crenshaw (1991), Vergès (2018), and Morrison (2019), in order to demonstrate, through a comparative perspective, the ways in which the experience of the colonial past affects the female body, which carries within itself stigmas, traumas and marks of oppression aggravated by factors such as gender, race and class. Both the characters Lucy and Célianne undergo a process of triple subordination as black and migrant women. Even though the colonized subjects are looked down upon and attempts are made to limit their performances, in both cases the characters resist and fight back to the attempts employed at silencing and erasing them.